Assessment of the efficacy of on-demand tegoprazan therapy in gastroesophageal reflux disease through a randomized controlled trial - Sun Hyung Kang; Hee Seok Moon; Jae Kyu Sung; Sun Moon Kim; Ki Bae Kim; Seung Woo Lee; Young Sin Cho; Ki Bae Bang; Kyung Ho Song (Scientific Reports)
Abstract In patients with gastroesophageal reflux disease (GERD) whose symptoms improve with acid-suppression therapy, on-demand treatment could constitute maintenance therapy. This study investigated the comparative efficacy and safety of on-demand tegoprazan and proton-pump inhibitor (PPI) therapy in GERD. From six university hospitals in the Daejeon-Chungcheong region, we enrolled patients with GERD who had experienced symptomatic improvement with acid-suppressive therapy and, using a randomization table, randomly allocated these participants to two groups: to receive either tegoprazan 50 mg + esomeprazole placebo or tegoprazan placebo + esomeprazole 20 mg, respectively. The primary endpoint of this study was the intergroup difference in patient satisfaction with on-demand therapy. Among the 69 participants who completed 8 weeks of on-demand therapy and rated patient satisfaction on a 5-point Likert scale, the tegoprazan and esomeprazole groups scored an average of 4.31 and 4.15 points, respectively, without any significant intergroup difference. In the tegoprazan group, 26.2% (182/694) of those with episodes experienced symptom improvement within 30 min, which is a significantly higher proportion compared to 16.1% (104/646) in the esomeprazole group. Compared to the esomeprazole group, the tegoprazan group had a significantly shorter time to symptom improvement overall and a significantly higher proportion of patients who improved within 30 min. No serious treatment-emergent adverse events were reported. Tegoprazan is effective as on-demand therapy for GERD and offers the expectation of faster symptom improvement than with PPIs. Clinical trial KCT0009296, registered at cris.nih.go.kr.